Characteristics of non-fatal fall injuries in rural India. Issue 3 (26th April 2010) - Dandona, Rakhi; Kumar, G Anil; Ivers, Rebecca; Joshi, Rohina; Neal, Bruce; Dandona, Lalit
Abstract : Background: Little is known about the context, risk factors and severity of non-fatal fall-related injury in India. Objective: To report these data for a rural population in the East and West Godavari districts of the Indian state of Andhra Pradesh. Methods: In a cross-sectional population-based survey, 3686 participants aged ≥30 years (83.6% participation) selected by stratified random sampling were interviewed in 44 villages. Participants recalled injuries in the preceding 12 months that required them to stay away from their usual daily duties for at least 1 day irrespective of whether medical attention was sought for that injury. Results: The annual incidence of non-fatal fall-related injury based on a 3-month recall period was 3.30% (95% CI 2.54% to 4.05%) and 9.22% (95% CI 7.74% to 10.69%) for men and women, respectively, with the incidence increasing with age. For the most recent non-fatal fall-related injury, the home was the most common place of injury for women, and the farm for men, with the former more likely to fall while climbing up/down (20.9%) compared with the latter (10.3%). Most falls were at the same level (71.7%) and slipping was the most common cause of fall (40%). Limbs (legs, 55%; hand/arm, 33.3%) were the most commonly injured body part. Fifty-six per cent reported seeking treatment outside home for injury, of whom 74.6% were women; and 8.4% reported being admitted to a hospital. Conclusion: Falls are a significant public health problem facing women in rural India. Fall prevention strategies should be explored and implemented within the Indian context.